Ultrawideband quadrature power divider employing double wireless via - Siti Zuraidah, Ibrahim; Marek Edward, Bialkowski; Abbosh, A. (Wiley Periodicals, Inc., 2012)
Link to publisher's homepage at http://onlinelibrary.wiley.com/